2021
DOI: 10.1007/s13311-021-01013-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabinoids on Sleep and their Therapeutic Potential for Sleep Disorders

Abstract: The recent trend for legalization of medicinal cannabis and cannabinoid-containing products, together with their soporific effects, has led to a surge of interest of their potential therapeutic role in the management of some common sleep disorders, such as insomnia, sleep disordered breathing, and restless legs syndrome, and less common disorders such as narcolepsy and parasomnias. Although much of the pre-clinical and clinical data were derived from studies with relatively small sample sizes and limited by bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
38

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 87 publications
2
39
1
38
Order By: Relevance
“…In a more recent study, 71% of participants cited improved sleep as a reason for the use of medicinal cannabis (Bonn-Miller et al , 2014). Realization of the strong hypnogenic effects of cannabis and cannabinoid drugs has led to a growing interest in their potential utility in the treatment of various sleep disorders including insomnia or nightmares associated with posttraumatic stress disorder (Kaul et al , 2021). Surprisingly, the effects of repeated or chronic cannabinoid use on sleep measures currently are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study, 71% of participants cited improved sleep as a reason for the use of medicinal cannabis (Bonn-Miller et al , 2014). Realization of the strong hypnogenic effects of cannabis and cannabinoid drugs has led to a growing interest in their potential utility in the treatment of various sleep disorders including insomnia or nightmares associated with posttraumatic stress disorder (Kaul et al , 2021). Surprisingly, the effects of repeated or chronic cannabinoid use on sleep measures currently are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that cannabinoid drugs can reliably alter sleep architecture in both humans and laboratory animals. Acute exposure to THC typically produces a pattern of increased sleep consolidation, increased slow-wave sleep (SWS), and decreased rapid-eye movement sleep (REM) (Kaul et al , 2021; Kesner and Lovinger, 2020). Results from studies of chronic cannabinoid exposure are variable but there is growing evidence for decreased total sleep time, decreased SWS, and a return to baseline levels of REM (Kaul et al , 2021; Kesner and Lovinger, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The literature examining the effects of cannabis on sleep duration, architecture, or quality in people with no sleep disturbances at baseline demonstrate overall mixed results. [5][6][7][8] Early polysomnographic studies suggest that even a single cannabis exposure can cause reduced sleep-onset latency, increased total sleep time, and less disruptions once asleep. 21 Repeated use can quickly demonstrate habituation and likely opposite effects: increased sleep-onset latency, decreased total sleep time, and greater sleep disruption.…”
Section: Discussionmentioning
confidence: 99%
“…7 8 In contrast to CBD, current evidence suggests that delta-9 tetrahydrocannabinol (THC), the other major cannabinoid present in most strains of cannabis, has stimulant and hallucinogenic properties contributing to sleep disruption. 8 With an evolving market of new cannabis strains and cannabinoid formulations, each with varying proportions of CBD and THC, the generalizability of the current literature about sleep impact is limited. Despite insomnia being one of the most cited reasons for selfmedication with cannabis or cannabinoids, the evidence base is overall inconsistent and of poor quality, as described in a recent systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation